Associations Between Interindividual Differences, Expectations and Placebo and Nocebo Effects in Itch - Meeuwis, Stefanie H.; van Middendorp, Henriët; Veldhuijzen, Dieuwke S.; Evers, Andrea W. M. (Frontiers in Psychology, 2021)
Introduction. Placebo and nocebo effects are positive and negative health outcomes that can be elicited by the psychosocial context. They can be mediated by expectations, and may emerge in somatic symptoms even when people are aware of these effects. Interindividual differences (e.g., in personality, affective states) could impact placebo and nocebo responding, but findings are inconsistent. Methods. The current work examined expectation as a mediator of the association between verbal placebo and nocebo suggestions (VSs) and histamine-induced itch across three experimental studies. Moreover, we examined whether interindividual differences (e.g., in optimism, neuroticism, behavioral activation system (BAS), body ignorance) modulated: 1) the direct association between VSs and itch (direct moderation), and 2) the indirect, expectation-mediated association between VSs and itch (moderated mediation). Positive VSs were compared to neutral instructions (Study 1; n=92) or negative VSs (Studies 2+3; n=203) in an open-label (i.e., explaining placebo and nocebo effects) or closed-label (concealed) context using PROCESS. First, mediation of VSs effects on itch by expectations was tested. Next, moderation by individual traits was explored using conditional process analyses. Results. The effects of VSs on itch were significantly mediated by expectation in Study 1 and in the open-label (but not closed-label) contexts of Studies 2&3. Ignorance of bodily signals marginally moderated the direct effects of VSs on itch when closed-label suggestions were given: at low levels of body ignorance, effects of positive and negative VSs were stronger. Moreover, moderated mediation was observed in the open-label groups of Studies 2&3: the expectation-mediated effects of VSs on itch were stronger when BAS drive was lower. Conclusion. Overall, the effects of VSs on itch were mediated by expectations in the open-label, but not the closed-label context. Moreover, the current work suggests that placebo and nocebo effects may be moderated by ignorance of bodily signals and the behavioral activation system (BAS). There was limited evidence that other interindividual differences modulated placebo and nocebo responding in itch.